GAMBARAN PERILAKU SELF-HARM SEBAGAI BENTUK EMOTION-FOCUSED COPING PADA REMAJA AKHIR - Yuna Yoniati; Ni Nyoman Ari Indra Dewi, Gretty Henofela Huwae (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
This study aims to describe self-harm behavior in late adolescents as a form of emotion- focused coping used to channel negative emotions. The research employed a qualitative design with a phenomenological approach to explore the subjective experiences of adolescents engaged in self-harm behavior. The subjects of this study were adolescents aged 18–22 years who continued to engage in self-harm, had not been diagnosed with personality disorders or other mental disorders, and engaged in self-harm with frequent occurrence based on DSM-5 criteria. Data were collected through semi-structured interviews, guided observations, and documentation. The findings reveal that self-harm behavior among late adolescents is a response to emotional pressures arising from internal factors, such as academic stress and inner conflict, as well as external factors, including parental pressure and lack of emotional support from the social environment. Self-harm functions as a maladaptive coping mechanism to express and alleviate negative emotions that are difficult to articulate verbally (emotion-focused coping). The study concludes that parental and environmental support is crucial in providing an open space for late adolescents to express their emotions, along with psychological interventions, such as regulation therapy, to help adolescents address self-harm behavior and develop adaptive coping mechanisms